2008
DOI: 10.1002/jbm.b.31215
|View full text |Cite
|
Sign up to set email alerts
|

The new adhesion prophylaxis membrane A‐part®—From in vitro testing to first in vivo results

Abstract: The properties of the A-part membrane suggest that it may be useful as an antiadhesive in surgery. A-part is effective in in vivo testing as determined in a rabbit sidewall model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…Pathologic angiogenesis occurs when the eff ect of stimulatory molecules outweighs the eff ect of inhibitory molecules. Intensive study has shown that the angiogenic process involves more than the simple proliferation of endothelial cells; it requires that endothelial cells to divide and invade the basement membrane, migrate, and undergo diff erentiation and capillary-tube formation [7,11] . This process is driven by angiogenic molecules as well as other factors, such as degradative enzymes, which mediate the above processes.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic angiogenesis occurs when the eff ect of stimulatory molecules outweighs the eff ect of inhibitory molecules. Intensive study has shown that the angiogenic process involves more than the simple proliferation of endothelial cells; it requires that endothelial cells to divide and invade the basement membrane, migrate, and undergo diff erentiation and capillary-tube formation [7,11] . This process is driven by angiogenic molecules as well as other factors, such as degradative enzymes, which mediate the above processes.…”
Section: Discussionmentioning
confidence: 99%
“…To improve quality of adherence of the barrier to the viscera, CMC was added to PVA gel. Jaenigen et al [14] showed in a rabbit sidewall model that this PVA-CMC gel diminishes adhesions compared with untreated controls and animals given 4% icodextrin. Lang et al [15] found similar results in their rabbit sidewall model; significantly fewer adhesions were present in rabbits treated with PVA-CMC gel than in those given 4% icodextrin and in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous products have been tested to minimize the formation of adhesions, based on barriers that separate the injured surfaces long enough to allow repair without adhesions. A new adhesion barrier consisting of polyvinyl alcohol (PVA) and carboxymethylcellulose (CMC) gel (A-Part Gel Ò ; Aesculap AG, B. Braun, Tuttlingen, Germany) has shown promising results in in vitro as well as in vivo studies [14][15][16]. However, in past years, several anti-adhesive agents have not entered widespread clinical use because of concerns about their interference with anastomotic site healing [17,18].…”
mentioning
confidence: 99%
“…A variety of experimental studies in different animal models have been conducted which showed that A-Part Gel ® is efficacious in the reduction of post-surgical adhesions in vivo [ 11 16 ]. Therefore, the aim of this study was clearly the evaluation of the safety and secondly an estimation of the efficacy of this hydrogel in the peritoneal adhesions prevention after primary elective laparotomy compared to an untreated control group in humans.…”
Section: Introductionmentioning
confidence: 99%